Cyber Deterrence strategies in the 21st century - Temur Digmelashvili; Lika Lagvilava (International Society of Philosophy and Cosmology, 2023)
The primary objective of this study is to analyze the historical evolution of cyber deterrence strategies, tracing their development from conventional defence paradigms to the contemporary digital domain. By examining case studies, policy frameworks, and international collaborations, the research aims to unearth the pivotal milestones and key transformations in the narrative of cyber deterrence. The 21st century has witnessed an unprecedented proliferation of cyber threats, underscoring the imperative for robust cyber deterrence strategies. This research study delves into the multifaceted landscape of cyber deterrence, aiming to elucidate its evolution, challenges, and future trajectories in an era defined by technological innovation and geopolitical complexities-furthermore, the research endeavours to offer insights into the future perspectives of cyber deterrence strategies. Anticipating future geopolitical shifts and the evolution of cyber threats, the study envisages adaptive strategies and policy recommendations to fortify cyber defences. The methodology involves a comprehensive review of scholarly literature, case analyses and policy documents. The synthesis of these diverse sources aims to present a holistic understanding of cyber deterrence strategies and their implications in the contemporary landscape. This article provides an overview of the research's scope, objectives, methodology, and anticipated contributions to the field of cybersecurity and international relations.